Perfil do migrante brasileiro - Adolfo Sachsida; Paulo Furtado de Castro; Mário Jorge Cardoso de Mendonça; Pedro H. Albuquerque (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper set up some stylized facts related to migration in Brazil. Two important things should be kept in mind: a) the data came from PNAD 2006; and b) the variable migration is defined as an individual that was born in one state but lives in another one. Changes in the definition of the variable migration or in the dataset are able to change the qualitativeresults. We can summarize our results in the following: 1) young individuals with higher level of education are more prone to migrate; 2) gender and race are important factors related to migration; and 3) distance between regions is a very important variable to explain migration.
Keywords: J1; J11; J19; 330